2018
DOI: 10.1093/brain/awy035
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of the normal intracranial electroencephalogram: neurophysiological awake activity in different cortical areas

Abstract: mcgill.ca).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
233
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 220 publications
(251 citation statements)
references
References 39 publications
16
233
1
1
Order By: Relevance
“…15,[17][18][19][20] As a Web-accessible resource, the Open MNI iEEG Atlas (https://mni-open-ieegatlas.research.mcgill.ca), has been made available via the LORIS neuroinformatics platform developed at the MNI. 15,[17][18][19][20] As a Web-accessible resource, the Open MNI iEEG Atlas (https://mni-open-ieegatlas.research.mcgill.ca), has been made available via the LORIS neuroinformatics platform developed at the MNI.…”
Section: Coregistration and Anatomical Localization Of Electrodes Andmentioning
confidence: 99%
See 2 more Smart Citations
“…15,[17][18][19][20] As a Web-accessible resource, the Open MNI iEEG Atlas (https://mni-open-ieegatlas.research.mcgill.ca), has been made available via the LORIS neuroinformatics platform developed at the MNI. 15,[17][18][19][20] As a Web-accessible resource, the Open MNI iEEG Atlas (https://mni-open-ieegatlas.research.mcgill.ca), has been made available via the LORIS neuroinformatics platform developed at the MNI.…”
Section: Coregistration and Anatomical Localization Of Electrodes Andmentioning
confidence: 99%
“…15 We merged some of these regions to increase the number of channels per region and hence the reliability of the results. 15 We merged some of these regions to increase the number of channels per region and hence the reliability of the results.…”
Section: Grouping Regions For Hfo Rate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…13 In fact, this study is the first to identify relative entropy in the ripple band to be the best-performing feature independent of the state of vigilance. 34,35 If this feature will be more frequently selected should it be normalized for region-specific spectral frequencies awaits further investigation. In signal processing, relative entropy reflects the randomness and spectral richness between two time-series and describes how entropy of one signal diverges from a second one.…”
Section: Feature Selectionmentioning
confidence: 99%
“…As an additional analysis, we determined whether anatomical variability in MI (>150 Hz & 3‐4 Hz) during slow‐wave sleep would exist among nonepileptic electrode sites, defined as those unaffected by magnetic resonance imaging (MRI) lesion, SOZ, or interictal spike discharges . We believed this analysis was necessary for validating the application of MI (>150 Hz & 3‐4 Hz) in presurgical evaluation, because previous studies of nonepileptic eloquent cortex reported that the degree of phase‐amplitude coupling between HFA and theta/alpha/beta activity was modulated by sensorimotor or cognitive tasks during wakefulness .…”
Section: Introductionmentioning
confidence: 99%